Susceptibility of silver birch (Betula pendula) to herbivorous insects is associated with the size and phenology of birch – implications for climate warming. Issue 2 (17th February 2017) - Heimonen, Kaisa; Valtonen, Anu; Kontunen-Soppela, Sari; Keski-Saari, Sarita; Rousi, Matti; Oksanen, Elina; Roininen, Heikki
ABSTRACT: Susceptibility of trees to herbivorous insects is often associated with the tree growth and phenology, both of which are sensitive to a warming climate. Therefore, changes in these traits may affect the intensity of herbivory on trees in the future. We grew silver birch ( Betula pendula ) populations differing in their growth and phenology in a common garden experiment, and studied the effect of these plant traits on the leaf herbivory, insect herbivore density and community composition of herbivores in two consecutive years, 2011 and 2012. Differences in size and the timing of growth cessation among the birch genotypes were related to differences in herbivore community compositions and herbivory. In 2011, the most intensive herbivore damage was observed on birch genotypes of small size, late bud burst and early growth cessation, and these genotypes originated from high-latitude populations. The differences among birch genotypes in their susceptibility to herbivore damage may lead to differences in their competitive abilities. While climate warming will affect phenology and growth of plants, our study shows, that it may indirectly affect herbivory and herbivore communities as well.